FCD Application of Landsat for Monitoring Mangrove in Central Kalimantan - Raden Mas Sukarna; Yulianto Sahid (Indonesian Journal of Geography, 2015)
A large amount of tropical mangrove forest in Indonesia has been lost due to rapid development in coastal areas, such as, aquaculture, industry, housing, and etc. Assessment of mangrove still mostly used conventional methods. It involves labor intensive, time consuming, high costs and impractical for use in large area. To answer these problems, this study aims to study accuracy and effectiveness of forest canopy density (FCD) model of Landsat for monitoring mangrove changes with large area ±2.600 hectares during periods 2002 and 2014 in Central Kalimantan. The result showed that FCD is capable to classified mangrove changes with overall accuracy 89.75%, and known that mangrove changes during approximately 12 years divided into four groups, i.e. deforested areas 11.11%, degraded areas 12.98%, regrowth areas 23.29% and not change areas 52.62%. Concluded that FCD model is quite accurate and effective used to monitor mangrove changes such as deforestation, degradation and regrowth.